PEMETAAN FOOD SECURITY ANTAR PROVINSI DI INDONESIA : GLOBAL FOOD SECURITY INDEX APPROACH - Jakaria; Tanuwijaya, Justine (JURNAL ILMIAH EDUNOMIKA, 2025)
This study was conducted with the aim of analysing the mapping of food security between provinces in Indonesia using the Global Food Security Index (GFSI) approach where the aspects or dimensions used include availability, affordability and utilization. The research method is carried out with a quantitative approach through indexing calculations by means of distance to scale, namely for each measurement indicator an index calculation will be carried out by comparing one province with another province as a benchmarking (reference). The results of the study show that during the 2020-2023 period, the food security index for all provinces is at a fairly good level, which has an average score of 70%. Bali Province consistently ranks first for Indonesia's food security index by province. West Papua and Papua provinces consistently ranked the lowest for Indonesia's provincial food security index. The source of the low level of food security in West Papua and Papua is the low achievement of the pillars of affordability and utilisation. Keywords : food security, availability, affordability, utilization, distance to scale.